Peningkatan Hasil Belajar Siswa melalui Penerapan Model Pembelajaran Kooperatif : (Tipe Student Teams Achievement Divisions) pada Mata Pelajaran Pendidikan Agama Islam , (Studi Kasus: Kelas IV SDN 1 Kraksaan kabupaten Probolinggo) - Hikmah, Dewi Wahyuning; Aliyah, Kholifatul (BAHTSUNA: Jurnal Penelitian Pendidikan Islam, 2019)
Abstract In connection with this vision, a set of principles for implementing education has been established to be the basis for implementing education reform. One of these principles is that education is held as a process of civilizing and empowering students that lasts throughout life (Rusman, 2010: 3). Islamic Religious Education is a religious education which is a condition of moral and commendable behavior. With the establishment of Islamic Religious Education is expected to be able to sustain the development of good character of students so as to produce educational products that are of perfect character. Further discussing some of the notions of Islamic Religious Education which include Islamic Religious Education is interpreted as a conscious and planned effort in preparing students to recognize, understand, appreciate to believe, have faith, and have good morals in practicing the teachings of Islam from its main source al- Qur'an and Hadith, through the activities of guidance, teaching, training, and the use of experience. Accompanied by guidance to respect adherents of other religions in relation to harmony between religious communities in the community to realize the unity and integrity of the nation Keywords: Islamic Religious Education, good morals